A hybrid OTA-C notch filter for physiological signal acquisition - Surachoke Thanapitak (2018)
© 2015 IEEE. In this paper, a hybrid OTA-C structure which consists of an ordinary differential OTA and a common drain is constructed as a fully differential notch filter for 50 Hz signal attenuation. The power consumption and linear range of this notch filter is 0.525 nW and 300 mVPP at 0.1% THD. This design only requires the total capacitance at 6.66 pF for the second order notch filter.